2022
DOI: 10.12968/bjnn.2022.18.sup3.s22
|View full text |Cite
|
Sign up to set email alerts
|

Multiple sclerosis, disease modifying therapies and pregnancy

Abstract: Multiple sclerosis (MS) affects women more commonly than men and is often diagnosed between 25 and 37 years of age. Therefore, at the time of diagnosis, many people have not finished trying for a family, and the person with MS often faces questions regarding their disease and the use of treatments when pregnant and breastfeeding. This review provides practical advice and guidance for MS and neurology nurses to help them support people with MS and their families throughout their family planning and pregnancy jo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…In addition, other concerns of women with MS regarding motherhood have been reported, including worries about transmitting MS to their fetus, how drugs taken to manage MS affects the health of their fetus, how MS may affect their ability to mother, and the effect of pregnancy and the postpartum period on the activity of the disease (Colaceci et al, 2021; Kosmala-Anderson & Wallace, 2013; Payne & McPherson, 2010; Prunty et al, 2008). Research has shown that it is possible for women with MS to have healthy pregnancies and give birth to healthy babies (Dobson et al, 2019; Judge-Clayden et al, 2022). For this reason, counseling and education about pregnancy to be given to women with MS is very important in eliminating their concerns.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, other concerns of women with MS regarding motherhood have been reported, including worries about transmitting MS to their fetus, how drugs taken to manage MS affects the health of their fetus, how MS may affect their ability to mother, and the effect of pregnancy and the postpartum period on the activity of the disease (Colaceci et al, 2021; Kosmala-Anderson & Wallace, 2013; Payne & McPherson, 2010; Prunty et al, 2008). Research has shown that it is possible for women with MS to have healthy pregnancies and give birth to healthy babies (Dobson et al, 2019; Judge-Clayden et al, 2022). For this reason, counseling and education about pregnancy to be given to women with MS is very important in eliminating their concerns.…”
Section: Introductionmentioning
confidence: 99%